1996
DOI: 10.1183/09031936.96.09020186
|View full text |Cite
|
Sign up to set email alerts
|

Differences in PO2 and PCO2 between arterial and arterialized earlobe samples

Abstract: Differences in PO 2 and PCO 2 between arterial and arterialized earlobe samples. A. Sauty, C. Uldry, L-F. Debétaz, P. Leuenberger, J-W. Fitting. ©ERS Journals Ltd 1996. ABSTRACT: Arterialized ear lobe blood samples have been described as adequate to gauge gas exchange in acute and chronically ill patients. It is a safe procedure, usually performed by medical technicians. We have conducted a prospective study to verify the validity of this method.One hundred and fifteen consecutive adult patients were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 12 publications
6
60
2
Order By: Relevance
“…Arterialized earlobe blood is said to be more suitable for clinical assessment of arterial pO 2 only for values < 60 mm Hg and less suitable for higher values due to underestimation of the real value [21]. Overall, our study seems to confirm that the techniques we used for evaluating most of the changes in blood chemistry, acid-base equilibrium [21], electrolyte and blood lactate are suitable for clinical assessment and for metabolic research at high altitude.…”
Section: Technical Csupporting
confidence: 73%
See 2 more Smart Citations
“…Arterialized earlobe blood is said to be more suitable for clinical assessment of arterial pO 2 only for values < 60 mm Hg and less suitable for higher values due to underestimation of the real value [21]. Overall, our study seems to confirm that the techniques we used for evaluating most of the changes in blood chemistry, acid-base equilibrium [21], electrolyte and blood lactate are suitable for clinical assessment and for metabolic research at high altitude.…”
Section: Technical Csupporting
confidence: 73%
“…Overall, our study seems to confirm that the techniques we used for evaluating most of the changes in blood chemistry, acid-base equilibrium [21], electrolyte and blood lactate are suitable for clinical assessment and for metabolic research at high altitude.…”
Section: Technical Csupporting
confidence: 62%
See 1 more Smart Citation
“…We read with great interest the paper by SAUTY et al [1] in the February issue of the Journal. They found that arterialized earlobe blood samples are in good agreement with arterial blood samples for carbon dioxide tension (PCO 2 ) but not for oxygen tension (PO 2 ), and rightly state that "arterialized earlobe blood PO 2 is not a reliable mirror of arterial PO 2 " in adults patients.…”
Section: To the Editormentioning
confidence: 82%
“…2 However, it is less useful in the acute setting because an adequate vasodilatation needs to be ensured, which typically lasts for at least 10 minutes. 1,2,[5][6][7] Different trials have evaluated the agreement between ABG and CBG in terms of PO 2 measurements, with conflicting results; whereas one trial reported close agreement between ABG-versus CBG-derived values over a wide range of PO 2 values, 7 other trials showed wide limits of agreement (LOA). 8,9 A 2007 meta-analysis comparing ABGs to CBGs emphasized that capillary PO 2 (P c O 2 ) (earlobe sampling) may be an appropriate replacement for arterial PO 2 (P a O 2 ); 2 however, the authors also pointed out that CBG might not be appropriate if precision is required, based on the fact that the residual standard error (SE) in the regression equation was 6 mmHg.…”
mentioning
confidence: 99%